Analysis of City Demographics in Turkiye Using Data Mining Techniques - Özge Doğuç; Kevser Şahinbaş; Gökhan Silahtaroğlu (Acta Infologica)
In this study, a data mining model has been developed and used to analyze how cities and regions in Turkey can be grouped, aiming to find similarities and differences between them. For this purpose, data is obtained from Turkish Statistical Institution (TUIK) and fuzzy c-means clustering algorithm was used to find categorizations. The data set contains 142 variables from 8 categories such as education, health, happiness, and development levels. The results showed that in all categories, the biggest 3 cities in Turkey, İstanbul, Ankara, and İzmir are different from the rest of the country. Also, cities located in the western and eastern regions of Turkey are mostly grouped among themselves, showing the clear distinction between those two regions. Finally, small cities with big neighbors are grouped with other big cities, showing the direct impact of big cities on their neighbors. This also implies that small cities with no big neighbors are often isolated, as their residents don’t have access to the services provided in the big cities.